Patterns of Antibiotic Prescription in Endodontic Therapy in the Republic of Croatia - Josipa Sović; Sanja Šegović; Božidar Pavelić; Ivona Bago; Ivana Šutej; Ivan Tomašić (MDPI AG, 2024)
In response to the global trend of decreasing antibiotic usage, this study aimed to evaluate the nature and frequency of antibiotic prescriptions in conjunction with endodontic therapy in Croatia and to assess the attitudes of Croatian dental practitioners towards the endodontic treatment of patients susceptible to bacterial endocarditis. A survey questionnaire was sent to all dental practitioners in Croatia, achieving a response rate of 27%. The most frequently prescribed antibiotic was penicillin with clavulanic acid (63.4%), while standalone penicillin was less prevalent (18.6%). For patients exhibiting penicillin allergies, 90% of respondents indicated clindamycin as their preferred alternative. Antibiotics were mostly prescribed for localized acute apical abscesses without fever, followed by prophylaxis for infectious endocarditis and cellulitis. Only 1.3% of the respondents reported frequent antibiotic prescriptions without accompanying local treatment. While a substantial proportion of surveyed practitioners professed familiarity with the latest guidelines for antibiotic prophylaxis, their choice of antibiotics did not consistently reflect this claim. Most respondents conducted endodontic procedures on patients at risk of bacterial endocarditis. The findings highlight a need for targeted continuing education for dental practitioners in the Republic of Croatia, ensuring their practices align with current guidelines and global trends in antibiotic prescription.